Bacterial Community and Fermentation Quality of Ensiling Alfalfa With Commercial Lactic Acid Bacterial Additives - Na, Na; Qili, Moge; Wu, Nier; Sun, Lin; Xu, Haiwen; Zhao, Yi; Wei, Xiaobin; Xue, Yanlin; Tao, Ya (Frontiers in Microbiology, 2022)
The aim of this study is to evaluate the effects of adding six common commercial lactic acid bacterial (LAB) additives (A1, Lactobacillus plantarum, L. buchneri, and Enterococcus faecalis; A2, L. plantarum and L. casei; A3, L. plantarum and L. buchneri; A4, L. plantarum, L. buchneri, L. casei, and Pediococcus acidilactici; A5, L. plantarum (producing feruloyl esterase); and A6, L. buchneri, P. acidilactici, β-glucanase, and Xylanase) on bacterial community and fermentation quality of alfalfa silage. The alfalfa was harvested at squaring stage, wilted on field for 24 h, and ensiled without any additives (Control) and with A1, A2, A3, A4, A5, and A6. The microbial counts, bacterial community, fermentation parameters, and nutrition compositions were determined after ensiling for 90 d. The total abundance of LAB genera in alfalfa pre-ensiling was 0.38% in bacterial community. The abundances of Lactobacillus, Enterococcus, and Pediococcus in Control silage were 42.18%, 40.18%, and 8.09% of abundance, respectively. Lactobacillus in A1-, A2-, A3-, A4-, and A5-treatments had 89.32%, 92.93%, 92.87%, 81.12%, and 80.44% of abundance, respectively; moreover, Pediococcus and Lactobacillus in A6-treatment had 70.14% and 24.86% of abundance, respectively. Compared with Control silage, LAB-treatments had lower pH, ammonia nitrogen, and water-soluble carbohydrates (P < 0.05). The A5- and A6-treatments contained lower neutral detergent fiber, acid detergent fiber, and hemicellulose than other treatments (P < 0.05). Overall, LAB genera were presented as minor taxa in alfalfa pre-ensiling and as dominant taxa in alfalfa silage. Adding LAB additives improved the fermentation quality and changed the bacterial community of alfalfa silage. The main bacterial genera in Control silage were Lactobacillus, Enterococcus, and Pediococcus. Lactobacillus dominated absolutely the bacterial communities of A1-, A2-, A3-, A4-, and A5-treatments; Pediococcus and Lactobacillus were dominant bacterial genera in A6-treatment. Inoculating A5 and A6 degraded the fiber in alfalfa silage.